A qualitative content analysis of peer mentoring video calls in adolescents with chronic illness. (May 2018) - Ahola Kohut, Sara; Stinson, Jennifer; Forgeron, Paula; van Wyk, Margaret; Harris, Lauren; Luca, Stephanie
This article endeavored to determine the topics of discussion during open-ended peer mentoring between adolescents and young adults living with chronic illness. This study occurred alongside a study of the iPeer2Peer Program. Fifty-two calls (7 mentor–mentee pairings) were audio recorded, transcribed verbatim, and analyzed using inductive coding with an additional 30 calls (21 mentor–mentee pairings) coded to ensure representativeness of the data. Three categories emerged: (1) illness impact (e.g., relationships, school/work, self-identity, personal stories), (2) self-management (e.g., treatment adherence, transition to adult care, coping strategies), and (3) non-illness-related adolescent issues (e.g., post-secondary goals, hobbies, social environments). Differences in discussed topics were noted between sexes and by diagnosis. Peer mentors provided informational, appraisal, and emotional support to adolescents.